Labour market institutions in small Pacific island countries: Main guidelines for labour market reforms - Miguel Á. Malo (Global Labor Organization (GLO), 2017)
This report consists of a comprehensive overview of labour market institutions in the small Pacific island countries in order to propose recommendations to improve the performance of their labour markets. We pay particular attention to three countries: Fiji, Palau and Papua New Guinea. We focus on the main pillars of labour market institutions, as employment protection legislation, minimum wage, and labour organization. The analysis considers the possibilities for institutional change in the next future. The main guidelines for eventual reforms are discussed, for the region as a whole and for the above three countries.
Keywords: J32; J51; J63; J80; K31; O17; O56; 330; Pacific; employment protection legislation; minimum wage; unions; institutions; labour law